Pig (Sus scrofa domesticus) dung and their associated fungi: Potential candidates for bio-remediation and nutrients improvement of crude oil contaminated soils - David Nwazuo Enyiukwu; INENESIT N. BASSEY; GRACE AMARACHI NWAOGU; N.U. ASAMUDO; LWANGA AZUBUIKE CHUKWU; E.A. MONDAY; JACQUELINE O. MARANZU (Society for Indonesian Biodiversity, 2021)
Abstract. Enyiukwu DN, Bassey IN, Nwaogu GA, Asamudo NU, Chukwu LA, Monday EA, Maranzu JO. 2021. Pig (Sus scrofa domesticus) dung and their associated fungi: Potential candidates for bio-remediation and nutrients improvement of crude oil contaminated soils. Biodiversitas 22: 3276-3286. Pig dung a common agro-waste material in Nigeria is associated with many fungal saprophytes. Rising oil spillages and pollution in Nigeria have made cultivation of affected agro-lands un-rewarding. Potentials of pig dung in mitigating crude oil pollution in agro-soils are herein studied. The objectives of this study were to characterize the fungal profile associated with wet and dry dung of pig. And to evaluate the remediating impacts of pig dung and their associated fungi on crude oil and heavy metals contents, physicochemical properties, and phytotoxicity of crude oil polluted soils. Coprophilous fungi were isolated from wet and dry dung by moist chamber technique and identified. Utisoil from Umudike was polluted with crude oil, amended with 10-40% of dry pig dung and sown with soybean (Glycine max L.). The amended and un-amended crude oil contaminated utisols were analyzed to reduce crude oil and heavy metals contents; and physicochemical properties at planting, and harvesting, respectively, using classical and spectrometric methods, and the extent of crude oil and heavy metals removal determined. The percentage germination, height, number of leaves, leaf color, vigor, and biomass of the test crop were recorded from the test plant. The results showed that Aspergillus candidus, Sclerotium sp., Absidia sp., Acremonium sp., Candida tropicalis, C. pseudotropicalis, and Rhizopus oryzae were consistently isolated from the dry dung specimen than the wet one. The results also indicated that the treatments significantly reduced the treated soils' crude oil and heavy metals contents. It revealed that values obtained for residual oil or heavy metals contents of the treated soils and crop performance were inversely and directly related to levels of soil amendment respectively. Crop performance in the amended soil remained statistically (P?0.05) higher compared to the control. Soil analyses showed that the dung treatments significantly increased the values of nitrogen, phosphorus, potassium, organic carbon, etc. in a directly proportional manner. Therefore, pig dung and their associated fungi hold strong potentials as cheap eco-friendly platforms to provide and stimulate microbial growth, hasten degradation and removal of crude oil and heavy metals from contaminated soils; and thus permit and sustain good performance of arable crops.